PENGGUNAAN MEDIA 3 DIMENSI PADA MATA PELAJARAN IPA BAB FOTOSINTESIS UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS IV DI MI ZAINUL ANWAR - Qiptiyah, Mariyatul; yaqin, Firdaus ainul (Universitas Islam Zainul Hasan Genggong, 2023)
This study aims to increase the learning interest of grade IV MI Zainul Anwar students by using 3-dimensional media in learning science in the photosynthesis chapter. The type of research used The type of research used is classroom action research (PTK) in collaboration with class IV teachers. The subjects of this study were fourth grade students, with the object of research on learning interest using 3-dimensional media in fourth grade students. The observation technique was used as a data collection technique to determine students' interest in learning. The data analysis used includes qualitative descriptive techniques and quantitative percentages of student learning interest. students. The results of the analysis of student interest in learning in the first observation amounted to 50%. Cycle I action experienced an increase in learning interest of 65.5% but still did not reach the full criteria of 75%. cycle I action student learning interest reached the full criteria of 75%. The results of cycle II student interest in learning have increased by 85.5%. So it can be said that it has reached the criteria for completeness in this study. From the research data, it can be concluded that the use of 3-dimensional media in learning science chapter photosynthesis class IV MI Zainul Anwar can increase student interest in learning.